Genomic and cDNA clones of the homeotic locus Antennapedia in Drosophila. - Garber, R L (1983)
Homeotic genes are involved in the control of developmental pathways: dominant mutations at the Antennapedia locus of Drosophila, for example, lead to replacement of the antennae on the head of the fly by mesothoracic legs. Using a combination of chromosome walking and jumping, we have cloned a DNA region from Drosophila containing Antennapedia. Five DNA inversion rearrangements which are associated with the Antennapedia mutant phenotype were localized within a 25-kb region. Genomic DNA sequences from this area were used as hybridization probes to screen cDNA libraries prepared from Drosophila embryonic and pupal poly(A)+ RNA. A 2.2-kb cDNA sequence (903) was isolated which appears to derive from at least four non-contiguous chromosomal regions that span 100 kb. It includes the positions of the inversion breakpoints. A second cDNA of 2.9 kb (909) is composed of sequences from at least three chromosomal regions, two of which are similar or identical to sequences contained in the 903 clone but the third is derived from genomic DNA within a putative 903 intron. The unusual size and complexity of this locus are discussed.